2021
DOI: 10.1111/1750-3841.15913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Revtech thermal processing on volatile organic compounds and chemical characteristics of split yellow pea (Pisum sativum L.) flour

Abstract: Yellow pea (Pisumsativum L.) is an economically rich source of nutrients with health-promoting effects. However, the consumption of pea ingredients is minimal due to their off-flavor characteristics. The present study investigated the effect of Revtech heat treatment on the chemical profile and volatile compounds in split yellow pea flour. Revtech treatment (RT) was applied at 140 • C with a residence time of 4 min in dry condition (RT 0%) and in the presence of 10% steam (RT 10%). Both thermal treatments resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 107 publications
(266 reference statements)
1
7
0
Order By: Relevance
“…LOX activity in yellow peas causes the production of VOCs from PUFAs which are associated with unpleasant aromas in pea flour. While other approaches like micronization and RevTech heat treatment have been demonstrated to diminish the unpleasant aromas of various pulse flours by totally or partially deactivating LOX activity ( Shariati-Ievari et al., 2016 ; Fahmi et al., 2021 ), these methods lack selectivity and can impact other enzymes in pulse flours. The utilization of CRISPR/Cas9 technology presents an excellent option to target PsLOX genes precisely for mutation thereby reducing LOX activity in pea flour and reducing the production of undesirable VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…LOX activity in yellow peas causes the production of VOCs from PUFAs which are associated with unpleasant aromas in pea flour. While other approaches like micronization and RevTech heat treatment have been demonstrated to diminish the unpleasant aromas of various pulse flours by totally or partially deactivating LOX activity ( Shariati-Ievari et al., 2016 ; Fahmi et al., 2021 ), these methods lack selectivity and can impact other enzymes in pulse flours. The utilization of CRISPR/Cas9 technology presents an excellent option to target PsLOX genes precisely for mutation thereby reducing LOX activity in pea flour and reducing the production of undesirable VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on pulse crops showed a different evolution of the aroma when heat treatment was applied, mainly due to the inactivation of the lipoxygenase enzyme, which is one of the factors responsible for development of off‐flavors 48,49 . Fahmi et al 50 . reported a significant decrease in the concentration of some compounds, such as pentanal, 1‐penten‐3‐ol, hexanal and heptanal, in response to the thermal treatment of yellow pea.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on pulse crops showed a different evolution of the aroma when heat treatment was applied, mainly due to the inactivation of the lipoxygenase enzyme, which is one of the factors responsible for development of off-flavors. 48,49 Fahmi et al 50 reported a significant decrease in the concentration of some compounds, such as pentanal, 1-penten-3-ol, hexanal and heptanal, in response to the thermal treatment of yellow pea. The slurry was characterized by a lower total amount of volatile compounds developed consequent to the lipoxygenase activity in respect to PCA-HG, probably due to the slurry preparation process, which involves thermal treatment at 80 °C for 40 min, which could have inactivated the lipoxygenase enzyme and helped the volatilization of the already present VOC.…”
Section: Volatile Profile and Sensory Features Of Pcasmentioning
confidence: 99%
“…Heat treatments such as roasting, blanching, micronization, and steam heating have shown to be effective in enhancing both the nutritional and sensory profiles of pulse-derived ingredients and legumes in general [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Our earlier work reported the efficacy of Revtech thermal processing in reducing the beany off-flavor in split yellow pea flour [ 61 ] and improving the consumer acceptability of white pan bread fortified with 20% pea flour [ 62 ].…”
Section: Introductionmentioning
confidence: 99%